ӨНДӨРНАРАН ОРДЫН АЛТНЫ ХҮДЭРЖИЛТ ҮҮССЭН ОРЧИН - Б., Тамир; Д., Доржготов; Л., Жаргал; Л., Оюунжаргал; Ж., Эрдэнэбаяр; Фирт, Харайлд (Geological Issues, 2022)
Undurnaran Au mineralization area is situated in Saikhandulaan ore district, the NE of the South Gobi Cu-Au metallogenic belt within South Mongolian metallogenic province. Geographically, it is located in Saikhandulaan subprovince area of Dornogovi province 500km SE of Ulaanbaatar, 50m SW of the province center and 45 km SE of the subprovince center. The region where the property lies in is poorly developed in infrastructure. As for regional structure, the deposit area occurs in the north part of South megablock and NE-SW oriented fault-bounded Mandakh terrane separated by Saikhandulaan fault to the north and Manlai-Mandakh depth fault to the south. Tectonics of the target area is characterized by Mandakh intrusive complex and Gunbayan formation volcanogenic units. The area is structurally extended to the NE and consists of vertical dipping rock units. The fault structure is subdivided into two systems because of general strike and subsequence of the structure development: a. NE-directed fault; b. NW-directed fault. Geology of the ore deposit is characterized by Early Carboniferous Gunbayan formation sedimentary-volcanogenic rock units (C1gb), and Late Carboniferous Mandakh intrusive complex (1 C2m). Mineralogy of igneous rocks spread over the study area is characterized by intermediate volcanogenic units such as andesite, andesidacite, dacite-andesite tuff lava, tuff breccia, intrusive units such as diorite, subalkaline diorite, microdiorite, diorite porphyry units. The ore minerals are quartz, ankerite, gold, pyrite and arsenopyrite forming spotty, stripped and impregnated textures of ore. The two types of ore developed with the minerals are Au-bearing pyrite-arsenopyrite and Au-pyrite-chalcopyrite and they are of silicate – calcareous composition. Apparently, Au ore quartz of the deposit was considered to be developed through three different generations. Fluid inclusions in quartz are really tiny in size as well as are of two phases: gas (V) and liquid (L). The 1st, 2nd and final generation quartzes of the ore-bearing solution transform into homogenic phases at the temperatures of 321.5°С, 204°С and 185°С, respectively. The amount of fluid salt is 1.7-6.7 weight % NaCl eq. Stable oxygen isotope is (δ18O 23.6‰) for the first generation quartz whereas it is (δ18O 15.7‰) for the second and the third generation quartzes. Hydrogen isotope analysis was conducted in Undurnaran deposit muscovite (sericite). Hydrogen isotope of the muscovite taken from the alteration zone is found to be (δD) -134. As a result of the fluid inclusion composition, temperature, oxygen and sulfur isotope characteristics this deposit is identified to be gold vein type of mesothermal origin.